Developing the content of distance learning courses on the basis of pedagogical design - Lytvyn, O. (Problems of Engineer-Pedagogical Education, 2021)
Developing the content of distance learning courses on the basis of pedagogical designʺ The article analyzes the principles and features of models of pedagogical design and identifies the general advantages of using models of pedagogical design in the development of the content of a distance course. An increase in the efficiency of the educational process on condition of introducing the developed maintenance of distance courses on the basis of certain principles and models of pedagogical design are theoretically substantiated. The main stages of the development of the content of a distance course on the basis of pedagogical design are determined, characterized and analyzed. In the modern world information space, there is a tendency to blur the line between traditional and distance education, because most people resort to the Internet in the learning process. Currently, the Internet has the opportunity to find any information, any area that may be of interest, engaging and useful. The issue of training modern students – future teachers of engineering disciplines – who are deeply aware of the development of all areas and opportunities of the Internet education is an urgent and important issue today. Modern students form an information-aware generation, i.e. the availability of electronic educational programs, textbooks, and tasks does not go beyond their usual life, their life "online". Information support in some cases helps students to acquire knowledge, skills, as well as to move up the career ladder. In connection with the rapid development of technology, educational information technology should develop at the same pace, distance and online education in particular. Distance education is an alternative that allows solving modern problems, providing rapid information development. The effectiveness, efficiency and applicability of any distance course directly depend on the proper planning, development and pedagogical design of the content of the Internet education. Theories of pedagogical design are important because they help to develop a vision of the educational process at the early stages of design. It is a vision of results (how knowledge and skills of learners will change after studying a distance course developed according to the principles, models and rules of pedagogical design) and means (how these changes can be facilitated). The question of features and approaches to the development of a distance course on the basis of pedagogical design is the purpose of this article.